2019
DOI: 10.1016/j.redox.2018.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of guanine-derived urinary biomarkers of oxidative stress, determined by LC-MS/MS

Abstract: A reliable and fast liquid chromatography-tandem mass spectrometry method has been developed for the simultaneous determination of three oxidized nucleic acid damage products in urine, 8-oxoguanine (8-oxoGua), 8-oxo-7,8-dihydro-2′-deoxyguanosine (8-oxodGuo) and 8-oxo-7,8-dihydroguanosine (8-oxoGuo). We applied this method to assess the effect of various urine workup procedures on the urinary concentrations of the oxidized nucleic acid products. Our results showed that frozen urine samples must be warmed (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 60 publications
3
44
0
Order By: Relevance
“…We observed differential effects on DNA and RNA oxidation, a phenomenon also observed after intervention with olive oil [33]. A recent study also found such a differential effect in diseases, however, favoring RNA oxidation as a marker [6]. The underlying mechanisms for the differences between DNA and RNA oxidation are not known in detail, and the exact origin of the oxidized nucleotides is still unclear [7], [8].…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…We observed differential effects on DNA and RNA oxidation, a phenomenon also observed after intervention with olive oil [33]. A recent study also found such a differential effect in diseases, however, favoring RNA oxidation as a marker [6]. The underlying mechanisms for the differences between DNA and RNA oxidation are not known in detail, and the exact origin of the oxidized nucleotides is still unclear [7], [8].…”
Section: Discussionsupporting
confidence: 51%
“…The exact source of 8-oxodG and 8-oxoGuo is still debatable. However, the current acceptable interpretation is that they reflect the rate of guanine oxidation in the nucleic acids and their precursor pools [5], [6], [7], [8]. Increased levels of 8-oxodG and 8-oxoGuo are associated with aging, smoking, type 2 diabetes mellitus (T2DM), hypertension, neurodegenerative diseases, cardiovascular disease (CVD) and certain cancers [4], [9], [10], [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…By means of these methods, a significant increase or no differences in the levels of DNA damage has been detected in the blood and urine of COPD patients compared to the controls; however, a significant increase has been found in sputum. [25,30,37,43,75,[92][93][94][95][96][97] (Table 2).…”
Section: Total Oxidant Statusmentioning
confidence: 99%
“…Secondary antibodies conjugated to Alexa fluorophores were purchased from Molecular Probes (Life Technologies). DAPI was used to stain nuclei [59]. For some co-localization experiments, when two primary antibodies were raised in rabbits, one of the primary antibodies was detected using the regular procedure, while the second primary antibody was conjugated with Alexa fluorophore 488 using a commercially available kit (Life Technologies) [60].…”
Section: Immunofluorescence and Confocal Microscopymentioning
confidence: 99%